The German social space and its homologies: National variation on a basic structure - Atkinson, Will; Schmitz, Andreas (Current Sociology, 2024)
This article constructs a comprehensive new model of the contemporary class structure of Germany. More specifically, inspired by Pierre Bourdieu's geometric conception of class relations and drawing on original survey data, it adopts multiple correspondence analysis paired with cluster analysis to chart the German social space', that is, the relational configuration of key forms of capital. It then explores correspondences with occupational groups, ethnic groups, other demographic features, lifestyle practices and tastes. The results disclose specific structuring effects of German peculiarities on the distribution of social power, including East West reunification and the long-running guestworker programme. More fundamentally, though, in its basic structure, the space resembles that mapped by Bourdieu in France and those documented by others elsewhere, suggesting common principles of social and symbolic differentiation among Western capitalist societies.
Keywords: Germany; Lifestyles; Multiple Correspondence Analysis; Class